1998
DOI: 10.1046/j.1365-2672.1998.853533.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Listeria monocytogenes in sea water and effect of exposure on thermal resistance

Abstract: . SM I TH . 1998. Survival, recoverability and sublethal injury of two strains of Listeria monocytogenes, Scott A and an environmental strain KM, on exposure to sea water at 12·8 or 20·8°C was determined using in situ diffusion chambers. Plate counts were used to assess recoverability and injury while 5-cyano-2,3-ditolyl tetrazolium chloride (CTC) reduction was used to determine respiratory activity. T 90 values (times for 10-fold decreases in numbers of recoverable cells) on non-selective medium (trypticase s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…1b). During further starvation, the proportion of cells with a vp decreased from 1.5U10 7 to 5.0U10 6 , but this decline (33%) was not consistent with the decrease in cell viability as estimated by cfu, where a 99.99% reduction in viability was observed (Fig. 1b).…”
Section: Cell Viability and Survival Of S Pyogenes In The Stationarymentioning
confidence: 81%
“…1b). During further starvation, the proportion of cells with a vp decreased from 1.5U10 7 to 5.0U10 6 , but this decline (33%) was not consistent with the decrease in cell viability as estimated by cfu, where a 99.99% reduction in viability was observed (Fig. 1b).…”
Section: Cell Viability and Survival Of S Pyogenes In The Stationarymentioning
confidence: 81%
“…However, while some studies don’t dispute that L. monocytogenes can be isolated from water, they do disregard it as an important source of contamination within fish farms (Jemmi and Keusch, 1994; Rorvik et al, 2000). More recent studies have also shown the survival of the pathogen in seawater, although many of these report that the survival of L. monocytogenes is strain and temperature dependent with lower temperatures correlating with higher survival (Bremer et al, 1998; Hsu et al, 2005; Hansen et al, 2006). However, besides temperature, other factors must also be considered for the survival of L. monocytogenes in seawater.…”
Section: Entry Of L Monocytogenes Into the Food Chainmentioning
confidence: 99%
“…Appropriate serial decimal dilutions were made in sterile physiological water. Counts of L. innocua were determined in triplicate using the drop-plate method (Bremer, Osborne, Kemp, & Smith, 1998) by platting cell suspension on selective medium for enumeration of Listeria (PALCAM, Difco Laboratories, Detroit, USA). Colonies were counted after 48 h incubation at 37°C.…”
Section: Microbiological Analyses Of Cheese Samplesmentioning
confidence: 99%